Use of Ab Initio Methods for the Interpretation of the Experimental IR Reflectance Spectra of Crystalline Compounds - De La Pierre, Marco; Orlando, R.; Dovesi, R. (Wiley, 2014)
It is shown that ab initio simulation can be used as a powerful complementary tool in the interpretation of the experimental reflectance spectra R(v) of crystalline compounds. Experimental frequencies and intensities are obtained from a best fit of R(v) with a set of damped harmonic oscillators, whose number and initial position in frequency can dramatically influence the final results, as the parameters are strongly correlated. Computed ab initio values for frequencies and intensities are accurate enough to represent an excellent starting point for the best fit process. Moreover, at variance with respect to experiment, simulation permits to identify all the symmetry allowed modes, also when characterized by low intensity or when close to a very intense peak. Overall, simulation-aided analysis of experimental spectra prevents from classifying combination modes as fundamental modes and permits to discard artifacts due to superposition of bands, background, and noise. Finally, it allows to (almost) completely characterize the set of fundamental modes.